LAYANAN PROSES PEMBELAJARAN PADA ANAK BERKESULITAN BELAJAR - Meta Silvia Novembli; Marlina Marlina; Martias Martias (Universitas Negeri Padang, 2015)
Abstrak: This research discusses about the service of learning process on learning difficulties at SDN 03 Air Dingin. The purpose of this research is to describe how do the services of learning difficulties. This research uses a study of qualitative approach with accumulation the data by interview, observation, and documentation study. The research result indicates that teachers is one of the causes of learning difficulties experienced by students Therefore, it was suggested to the teachers to understand more about the students’ characteristics and the problem they encountered in the learning process.Key: learning services; learning difficulties